2006
DOI: 10.1074/jbc.m600749200
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Targeting of RGS9-2 Is Controlled by Multiple Molecular Determinants on Its Membrane Anchor, R7BP

Abstract: RGS9-2, a member of the R7 regulators of G protein signaling (RGS) protein family of neuronal RGS, is a critical regulator of G protein signaling. In striatal neurons, RGS9-2 is tightly associated with a novel palmitoylated protein, R7BP (R7 family binding protein). Here we report that R7BP acts to target the localization of RGS9-2 to the plasma membrane. Examination of the subcellular distribution in native striatal neurons revealed that both R7BP and RGS9-2 are almost entirely associated with the neuronal me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
74
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 44 publications
6
74
0
Order By: Relevance
“…We focus on elucidating the function of R7 RGS binding protein (R7BP), a palmitoylated SNARE-like protein that has been suggested to function as a membrane anchor, scaffold, or allosteric regulator for R7-RGS/Gβ5 complexes (24)(25)(26)(27)(28). Our studies support a model in which GIRK modulation occurs by channel assembly with R7-RGS/Gβ5 complexes that are allosterically regulated by R7BP.…”
mentioning
confidence: 71%
“…We focus on elucidating the function of R7 RGS binding protein (R7BP), a palmitoylated SNARE-like protein that has been suggested to function as a membrane anchor, scaffold, or allosteric regulator for R7-RGS/Gβ5 complexes (24)(25)(26)(27)(28). Our studies support a model in which GIRK modulation occurs by channel assembly with R7-RGS/Gβ5 complexes that are allosterically regulated by R7BP.…”
mentioning
confidence: 71%
“…Thus, R9AP is essential for normal photoresponse kinetics in both cell types (10,20,21). In contrast, R7BP is expressed widely in the nervous system, binds each R7 isoform, lacks a transmembrane domain, and associates with membranes by covalent attachment of the fatty acid palmitate to two C-terminal cysteine residues (22)(23)(24). In striatum, R7BP stabilizes RGS9 expression and function as a regulator of motor coordination and locomotor response to morphine (25).…”
mentioning
confidence: 99%
“…On the one hand, R7BP is palmitoylated efficiently because at steady state it associates nearly exclusively with membrane fractions of brain extracts (24,26). On the other, steady state nuclear accumulation of RGS7 and G␤5 in neurons appears to depend partially on R7BP (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…R7BP is a neuronal protein that anchors RGS proteins of the R7 family as a complex with G␤5 (12). Previously it was reported that R7BP interacts with RGS9-2 in the DEP domain and renders its localization on the plasma membrane (42). As shown in Fig.…”
Section: Rgs9mentioning
confidence: 99%